Adaptive Financing Pattern for Small Scale Fisheries with Case Study of Pajeko Fisheries in Bitung - Fini Lovita; Arif Satria; Dedi Budiman Hakim (School of Business, Bogor Agricultural University (SB-IPB), 2020)
he agriculture, forestry, and fisheries sectors have a share of 22.05% with 4.21% growth in North Sulawesi. The fisheries sub-sector dominates by 30%. The disbursement of banking institutions' credit for the sector increased by 35% in 2015-2017 but absorbs only 7% of total loans disbursed. The reluctance of formal financial institutions to provide credit to improve small fisheries has increased in non-formal financing. This study identifies factors influencing financing sources choice, comparison of bank and non-bank financing sources, and recommend adaptive financing patterns for small fisheries. Based on descriptive qualitative analysis of in-depth interviews with 32 respondents from 85 Pajeko fishers (mini purse seine) in the Bitung Oceanic Fishing Port (PPS), concluded that 97% of Pajeko fishers in Bitung chose non-bank to finance their operation with determinant factors of financial source: (i) easiness administration (88%), (ii) payment flexibility (78%), and (iii) collateral (69%). The result of comparison simulation shows that boat owner financing with profit sharing for three (boat, boat owner, crews) is the most profitable for the boat owner, while bank loan financing with profit sharing for two (boat owner, crews) is the most profitable for crews. Accordingly, an adaptive financing strategy development is recommended for banking institutions based on influencing factors of fisher’s choices and Pajeko fisher’s characteristics-based approach. Keywords: Pajeko fishery, resource of financing, bank financing source, non-bank financing source, adaptive financing